Automated Verification of IGRT‐based Patient Positioning. (8th November 2015) - Jiang, Xiaojun; Fox, Tim; Cordova, James S.; Schreibmann, Eduard
Abstract : A system for automated quality assurance in radiotherapy of a therapist's registration was designed and tested in clinical practice. The approach compliments the clinical software's automated registration in terms of algorithm configuration and performance, and constitutes a practical approach for ensuring safe patient setups. Per our convergence analysis, evolutionary algorithms perform better in finding the global optima of the cost function with discrepancies from a deterministic optimizer seen sporadically. PACS number(s): 87.55.Qr, 87.55.T, 87.55.N